Long-Term Population and Distribution Dynamics of an Endangered Irrawaddy Dolphin Population in Balikpapan Bay, Indonesia in Response to Coastal Development - Kreb, Danielle; Lhota, Stanislav; Porter, Lindsay; Redman, Alexandra; Susanti, Imelda; Lazecky, Milan (Frontiers in Marine Science, 2020)
Worldwide, cetaceans are impacted by human activities and those populations that occur in shallow-nearshore habitats are particularly vulnerable. We present the results of the first long-term study on the responses of a coastal population of endangered Irrawaddy dolphins to widespread habitat changes. We particularly investigated their responses in terms of distribution and abundance. Boat-based, line-transect surveys were conducted during 12 discrete survey periods in 7 surveys years spanning a 15-year period (totaling 78 days and 4,630 km of effort) in Balikpapan Bay, East Kalimantan, Indonesia. Irrawaddy dolphins were sighted on 136 occasions. Through DISTANCE analysis, a decrease in population density in the inner bay area was observed from 0.45 dolphins/km2 in 2000-2001 (CV=24%) to 0.34 and 0.32 dolphins/km2 in 2008 and 2015 (CV=31% & 25%). A shift in distribution was noted between the periods 2000-2002 and 2008-2015 with significantly lower occurrence in the lower bay segment compared to upper bay segments. No sightings were made in the outer bay area in later years, which coincided with increased shipping traffic in these areas. A peak in stranding events in 2016 and 2018 followed extremely high phenol levels within bay waters in 2015 and a large-scale oil spill in 2018. The mean annual mortality rates of 0.67 Irrawaddy dolphins/ year is unsustainable based on the lower potential biological removal (PBR) values for best abundance estimates of 2015 (Ndistance = 45 and Nmark-recapture = 73). Other threats to local dolphins include unsustainable fishing, underwater noise caused by unmonitored piling driven constructions, and chemical pollution. The research helped to identify Balikpapan Bay as an Important Marine Mammal Area by the IUCN MMPA Taskforce. Serious concerns remain for the concrete plans to move Indonesia’s capital city to the area north of the bay, in terms of increased shipping traffic and harbor construction in the upper bay segments that represent primary dolphin habitat. We recommend that protected areas will be assigned for marine mammals and artisanal fisheries while shipping traffic and piling activities be excluded from these areas. We also recommend a legislated requirement of a mitigation protocol compulsory for piling and seismic activities within Indonesia.